2022
DOI: 10.1021/acsaelm.2c01171
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Effect of Stretchable a-InGaZnO TFT on PI/PDMS Substrate under Repetitive Uni/Biaxial Elongation Stress

Abstract: We examine the fatigue effects of repeated elongation stress for a fabricated a-IGZO thin-film transistor (TFT) on an island polyimide (PI)/poly(dimethylsiloxane) (PDMS) substrate. The repeated elongation stress evaluation was performed in both a uniaxial direction with 10, 30, and 50% strain and biaxial direction with 10, 20, and 30% strain for 50 000 cycles. The a-IGZO TFTs on the island PI exhibit the following parameters: Vth : −0.91 ± 0.30 V, μ sat : 26.3 ± 0.61 cm2/(V s), and SS: 0.40 ± 0.02 V/decade. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In general, accumulated tensile stress induces a negative V th shift in TFT, [12,59] however, the micro-LED on the backplane might have been damaged by the biaxial stretching cycles, resulting in the failure of I DD . It was confirmed that there was negligible degradation in the on-state I DD under variations in VDD and V Data , as shown in Figure S12 (Supporting Information).…”
Section: Changes In Morphology and Electrical Characteristics Of Liqu...mentioning
confidence: 99%
See 2 more Smart Citations
“…In general, accumulated tensile stress induces a negative V th shift in TFT, [12,59] however, the micro-LED on the backplane might have been damaged by the biaxial stretching cycles, resulting in the failure of I DD . It was confirmed that there was negligible degradation in the on-state I DD under variations in VDD and V Data , as shown in Figure S12 (Supporting Information).…”
Section: Changes In Morphology and Electrical Characteristics Of Liqu...mentioning
confidence: 99%
“…In general, the accumulated tensile stress induces a negative V th shift in TFT due to oxygen vacancy generation, resulting in a current increase. [12,59] However, micro-LED on pixel circuit degrades with increasing stretching cycles. Thus, the deterioration could be attributed to the LED/island interfacial bonding reliability.…”
Section: Changes In Morphology and Electrical Characteristics Of Liqu...mentioning
confidence: 99%
See 1 more Smart Citation
“…As illustrated in Figure , the empty space between the normal pixels is occupied by the activated hidden pixels, thus preventing the loss of resolution and luminance during stretching . Such an idea was conceptually demonstrated in a simple passive-matrix (PM) LED pixel array, where the activation of hidden pixels was controlled by integrating additional strain sensors outside the array. ,, These sensors, which are typically designed with a positive gauge factor (P-GF) that increases resistance upon stretching, inevitably require complex signal processing to facilitate current flow and trigger the activation of the hidden pixels by the elongation of the substrates. For further advancement, key technologies compatible with pixel circuits arranged with numerous TFTs are essentially required to enable the application of this design concept to commercially available active-matrix (AM) displays …”
Section: Introductionmentioning
confidence: 99%
“…However, stretchable displays must satisfy stricter requirements than those imposed on existing flexible or foldable displays to maintain their electrical and optical properties under mechanical stretching. , While commercial products with flexible or foldable displays have recently emerged, the absence of commercial products with stretchable displays indicates an even more challenging technological hurdle. This difficulty arises from variations in the net display area, not during folding conditions but during stretching conditions . Therefore, most components of stretchable displays including light-emitting diodes (LEDs), thin-film transistors (TFTs), dielectrics, interconnects, encapsulations, and substrates should all be designed to withstand mechanical strain.…”
Section: Introductionmentioning
confidence: 99%